Similarities and disparities between Romanian individual and consolidated financial group statements - Florentin Tanasa; Doina Prodan (Studies and Scientific Researches: Economics Edition, 2012)
The purpose of this study is to identify, analyse and assess the main connections and implications of consolidated accounts on enterprise economy. Appearance of consolidated financial statements is intrinsically linked to certain concepts, such as group, control, the perimeter of consolidation, percentages of interests, methods of consolidation, or restatements. For a more complete view regarding consolidated annual accounts, it is necessary to delimit and define these particular elements. This approach targets the presentation of our vision over positioning, place and function of financial consolidated statements in the process of the financial report. The study envisages a summary and comparison of ideas found on this subject in thespecialty literature, the regulations developed by various international bodies. Thus, we think it will facilitate the correct positioning of the consolidated financial statements and the consolidated accounts’ concepts. To achieve the proposed desiderates, we have used a constructive methodology for identifying disagreements, approvals and development of a speech to more efficient and effective management of the mentioned concepts.